Absence of the Fourth Tendon of the Flexor Digitorum Brevis Muscle: A Cadaveric Study. Issue 4 (August 2013) - Bernhard, Andrew; Miller, Josh; Keeler, Jason; Siesel, Kathy; Bridges, Evan
This study was undertaken to help confirm the percentages concerning the presence or absence of the flexor digitorum brevis muscle tendon to the fifth toe. We also hope to be able to determine the presence based on gender and nationality. It is known to be absent occasionally; however, there is no definitive study dedicated to its prevalence. Using a pool of 60 cadavers, 97 total feet were included in our analysis. Of these feet, 47 (48%) lacked a flexor digitorum brevis tendon to the fifth toe at all. Furthermore, 25 (26%) had notably small tendons to the fifth toe. The final 25 (26%) had what the researchers deemed present tendons. This information could be helpful in surgical planning, including tendon transfer techniques, and biomechanical evaluations. Further research would need to be conducted as this was a cadaveric study. Levels of Evidence : Cadaver/anatomy research, Level V